Targeting SNARE-Mediated Vesicle Transport to Block Invadopodium-Based Cancer Cell Invasion - Gorshtein, Genya; Grafinger, Olivia; Coppolino, Marc G. (Frontiers in Oncology, 2021)
During metastasis, cancer cells can invade extracellular matrix (ECM) through a process mediated by matrix-degrading protrusions of the plasma membrane, termed invadopodia. Formation of invadopodia correlates with cells’ invasive and metastatic potential, and thus presents a potential target for therapeutic approaches to target metastatic progression. Invadopodia formation is dependent on the recruitment of proteins involved in intracellular signalling, actin cytoskeleton remodelling, and proteolytic matrix modification. The latter includes matrix degrading enzymes such as MT1-MMP, MMP2, and MMP9. These essential invadopodium-associated enzymes are required for localized matrix degradation, and their localization at invadopodia is central to invadopodium-based cancer cell invasion. Soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) facilitate intracellular vesicle traffic, including that involved in the transport of invadopodium-associated proteins, and in so doing promote modification of ECM and modulation of signaling pathways involved in the movement of cancer cells. Specific SNARE complexes have been found to support invadopodia formation, and these complexes are, in turn, regulated by associated proteins that interact specifically with SNAREs. Targeting SNARE regulatory proteins thus provides a possible approach to disrupt SNARE-dependent delivery of invadopodial proteins, including MT1-MMP, to sites of ECM modification. Here, we review recent studies of SNARE regulators that hold potential as targets for the development of anti-metastatic therapies for patients burdened with invadopodia-forming cancer types.